Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The role of international non-governmental organizations in non-international armed conflicts Lawyer / Raad Muhammad Hassan Al-Badri 2. Measuring the desire of the Employees of the Ministry of Hajj and Umrah in Saudi Arabia to implement Kaizen Mrs. Nesreen Abdul-Raheem Siddiq, Dr. Zenah Mahmoud Al-Kubaisy 3. Fifth-generation wars and their impact on international peace and security: "The Russian-Ukrainian war as a model" Dr. Badr Abdellah Bourouihiya 4. The effectiveness of social media sites in achieving customer satisfaction in The Kingdom of Saudi Arabia, 2023 Dr. Tareg Mohamed Elmahei Elbashier 5. The impact of transformational leadership on the effectiveness of decision-making: An Applied Study on General Hospital Mr. Yousef Dwaihi Al-Barakani 6. Identifying the reality of training at King Khalid University and its effects on improving performance through job satisfaction among employees Asst-Prof. Mohamed Ahmed Alsadig, Lecturer Abdallah Mushabab Omran 7. Roles of e-Management Systems in School Administration to keep pace with Vision 2030 of KSA in Makkah (2022) Mrs. Badriah Mohammad Muner Alotaibi